How does economic risk aversion affect biodiversity?. Issue 1 (1st January 2013) - Mouysset, L.; Doyen, L.; Jiguet, F.
Abstract : Significant decline of biodiversity in farmlands has been reported for several decades. To limit the negative impact of agriculture, many agro‐environmental schemes have been implemented, but their effectiveness remains controversial. In this context, the study of economic drivers is helpful to understand the role played by farming on biodiversity. The present paper analyzes the impact of risk aversion on farmland biodiversity. Here "risk aversion" means a cautious behavior of farmers facing uncertainty. We develop a bio‐economic model that articulates bird community dynamics and representative farmers selecting land uses within an uncertain macro‐economic context. It is specialized and calibrated at a regional scale for France through national databases. The influence of risk aversion is assessed on ecological, agricultural, and economic outputs through projections at the 2050 horizon. A high enough risk aversion appears sufficient to both manage economic risk and promote ecological performance. This occurs through a diversification mechanism on regional land uses. However, economic calibration leads to a weak risk‐aversion parameter, which is consistent with the current decline of farmland birds. Spatial disparities however suggest that public incentives could be necessary to reinforce the diversification and bio‐economic effectiveness.